STEAM class-based creative thinking ability instruments for elementary school - Ahmad Fadhlilah; Rochmiyati Rochmiyati; Lilik Sabdaningtyas (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
The aim of this study was to analyze the need for developing appropriate science, technology, engineering, arts and mathematics (STEAM) assessment instruments (vaild, practical and effective) to improve students’ creative thinking skills. The instruments that have been used in education units have not been fully able to encourage students to think at a higher level in building conceptual understanding and solving their own problems. This study used qualitative descriptive study based on a literature review of the STEAM-based assessment instrument as an effort to improve students’ creative thinking skills. The research subjects were educators and fourth grade students of SD Negeri 2 Tulusrejo, Pekalongan District, East Lampung. The research object was creative thinking ability, assessment instrument, and STEAM. The data collection instrument used an interview guide. Questionnaire. An assessment instrument needed to support the learning process in the education unit to improve students’ creative thinking skills. The finding indicated that educators had not fully used assessment instruments that could improve students’ creative thinking skills. Besides, educators needed a STEAM-based assessment instrument that was appropriate to the level of the learner. Thus, it can be concluded that STEAM-based instruments to improve students' creative thinking skills in elementary schools must be developed.